2015
DOI: 10.1016/j.reprotox.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicogenomic responses to phthalate ester exposure in an organotypic testis co-culture model and responses observed in vivo

Abstract: We have developed a three-dimensional testicular co-culture system (3D-TCS) which mimics in vivo testes. In this study, transcriptomic responses to phthalate esters (PE’s) were compared in the 3D-TCS with responses in rat testes in vivo. Microarray data from the 3D-TCS and from in vivo testes were used to compare changes in gene expression patterns after exposure to developmentally toxic (DTPE) or developmentally non-toxic (DNTPE) phthalate esters. DTPE treatments clustered separately from DNTPE treatments bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Treatment with a variety of toxicants has indicated that the 3D-TCS captures multiple modes of action for testicular toxicity. These include activation of cell death pathways (cadmium) as well as impacts on testosterone production and steroidogenic gene expression (phthalates) (Yu et al 2008, 2009, Wegner et al 2014, Harris et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Treatment with a variety of toxicants has indicated that the 3D-TCS captures multiple modes of action for testicular toxicity. These include activation of cell death pathways (cadmium) as well as impacts on testosterone production and steroidogenic gene expression (phthalates) (Yu et al 2008, 2009, Wegner et al 2014, Harris et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Self-renewal and progeny production of spermatogonia are controlled by the neighboring differentiated cells and extracellular matrix (ECM), known as substrate in vivo niches, while Sertoli cells are required for successful differentiation of germ cells in vitro culture systems (Griswold, 1998). The ECM Matrigel-based primary testicular cell model was reported to form a testicular-like multilayered architecture that mimics in vivo characteristics of seminiferous tubules (Harris et al, 2015;Wegner et al, 2013Wegner et al, , 2014Yu et al, 2005Yu et al, , 2008Yu et al, , 2009. As previously demonstrated, this model differentially responds to various phthalate exposures with changes in several cellular pathways, showing sensitive response to testicular toxicity (Harris et al, 2015;Yu et al, 2009).…”
mentioning
confidence: 99%
“…There is thus an urgent need to develop effective and practical tools for early screening of chemicals with potential adverse effects using highthroughput, low-cost methodologies that ensure high predictability of human biological responses (Parks Saldutti et al, 2013). Recently, in vitro testicular models have been introduced to environmental chemical safety assessment to improve the predictability of chemical-induced testicular toxicity in human and elucidate mechanisms of chemical toxicity (Harris et al, 2015;Hofmann et al, 2005a;Parks Saldutti, et al, 2013;Wegner et al, 2013Wegner et al, , 2014Yu et al, 2003Yu et al, , 2005Yu et al, , 2009). Some of these in vitro models form a testicular-like multilayered architecture that mimics in vivo characteristics of seminiferous tubules (Yu et al, 2003(Yu et al, , 2005.…”
mentioning
confidence: 99%